"Ice" juice from apples obtained by pressing at subzero temperatures of apples pretreated by pulsed electric fields. (February 2016) - Carbonell-Capella, Juana M.; Parniakov, Oleksii; Barba, Francisco J.; Grimi, Nabil; Bals, Olivier; Lebovka, Nikolai; Vorobiev, Eugene
Abstract: The impact of apple pretreatment by pulsed electric field (PEF) on juice extraction using the freezing-assisted pressing was studied. Apple discs were PEF pretreated at electric field strength of E = 800 V/cm and then air blast frozen inside the freezer (− 40 °C). Then, pressing experiments in a laboratory-pressing chamber (2–5 bars) were started at sub-zero temperature (− 5 °C). Time evolution of juice yield and its nutritional qualities were compared for PEF and untreated apple samples. High improvements of juice yield were obtained for freeze-thawed (FT) and PEF + FT samples. The combination of PEF + pressing (5 bar) at sub-zero temperature gave optimum results for juice extraction with high levels of carbohydrates, and antioxidant bioactive compounds. At fixed value of extraction yield, Y, PEF pretreatment improved nutritional parameters. E.g., at Y = 0.6, an increase in °Brix (by ≈ 1.27), carbohydrates (by ≈ 1.42), total phenolic compounds (by ≈ 1.16), flavonoids (by ≈ 1.09) and antioxidant capacity (by ≈ 1.29) was observed after PEF pretreatment. Industrial relevance: Pressing constitutes one of the most commonly used technologies at industrial scale to obtain fruit juices. However, during the pressing some undesirable chemical, physical and biological changes may occur in juices, thus reducing their nutritional and sensorial properties. For instance, the use of freezing-assisted pressing is a promising technique for the production of juice concentrates rich in sugars and other solids as the low temperature operation prevents undesirable modifications. But this method is rather expensive and requires strong control of the quality of "ice" juices, their sensory and compositional profiles. Thus, there is an increased search for obtaining new efficient methodologies for producing high quality juices. In this line, PEF-assisted pressing has been shown as a useful technology to increase juice yield. Therefore, the combination of PEF-assisted "ice" juice extraction by pressing of fruits at subzero temperatures may be a useful tool to improve the extraction yield of juices, thus improving their nutritional, physicochemical and sensorial properties. Keywords: "Ice" juice, Apple, Pulsed electric fields, Freezing-assisted pressing Highlights: PEF-assisted apple "ice" juice was extracted by pressing at subzero temperatures. Electroporation impact on freezing and pressing–thawing process was studied. PEF pretreatment of apples improved yields of juice at sub-zero temperatures. "Ice" juice from apples pretreated by PEF had higher bioactive compounds content.